# Solving an equation means finding the value that makes the statement true. solve this equation to find

###### Question:

8x − 8 = 4x + 12

## Answers

x = 5

Step-by-step explanation:

8x - 8 = 4x + 12

+8 +8

8x = 4x + 20

-4x -4x + 20

4x = 20

4x/4 20/4

x = 5

[tex]\frac{(-2)^{5x-3}}{(-2)^{2x}} =(-2)^{21}[/tex]

[tex](-2)^{5x-3-2x}=(-2)^{21}[/tex] (The numerator and the denominator has same bases, therefore the powers will get subtracted. It is an exponential property)

[tex](-2)^{3x-3}=(-2)^{21}[/tex]

[tex]3x-3=21[/tex] (As the left hand side is equal to right hand side and the bases are on both the sides are equal too, we will equate their exponential power. Another property)

[tex]x-1=7[/tex]

[tex]x=8[/tex] (After simplifying more, you'll get this)

8x − 8 = 4x + 12

Add 8 to both sides:

8x = 4x + 20

Subtract 4x from both sides:

4x = 20

Divide both sides by 4:

x = 20/4

x = 5

answer:

x=5

step-by-step explanation:

The answer is C. 5.6.

First combine the like terms of the equation.

6+5.6-x=6

6+5.6=11.6

11.6-x=6

Then subtract 11.6 from both sides of the equation.

11.6-11.6-x=6-11.6

-x=-5.6

Then divide both sides by -1.

[tex]\frac{-x}{-1}[/tex]=[tex]\frac{-5.6}{-1}[/tex]

x=5.6

x = 5

Step-by-step explanation:

8x - 8 = 4x + 12

8x - 4x = +12 + 8

4x = 20

x = 20/4

= 5

Therefore, x = 5

Hope this helped

:)

x=5

Step-by-step explanation:

First combine like terms

8x-8=4x+12

Move -8 over to the other side, it becomes +8

8x=4x+20

Now subtract 4x from 8x

4x=20

Now divide

20÷4=5

x=5

C is the correct answer

First, let's simplify:

11.6 - x = 6

Subtract:

-x = -5.6

Divide both sides by -1:

x = 5.6

Here's how you can solve the equation:

[tex]43 = 16 + 3x \\ 43 - 16 = 3x \\ 27 = 3x \\ x = \frac{27}{3} \\ x = 9[/tex]

Thus the answer is C.9

Hope it helps!